Formation and evolution of soil salinization based on multivariate statistical methods in Ningxia Plain, China - Liu, Zhenlin; Gao, Maosheng; Sun, Qiming; Hou, Guohua; Zhao, Yinxin (Frontiers in Earth Science, 2023)
The Ningxia Plain, situated in the arid zone of northwest China, is a typical dryland plain that faces significant challenges to sustainable agricultural development due to soil salinization. In this study, we employed multivariate analysis and geostatistical methods to investigate the degree and distribution types of soil salinization and the hydrochemical characteristics of shallow groundwater. We also examined the relationship between soil salinization and hydrogeochemical characteristics by analyzing the sources of groundwater ions. This study developed a hydrogeochemical model to describe the soil salinization process in the Ningxia Plain. The results indicate that the majority of surface soils are alkaline type soils, followed by chloride-sulfate type soils. The groundwater is mainly fresh water and brackish water, with a hydrochemical type of SO4·HCO3–Ca·Mg or SO4·Cl–Ca·Mg. Saline water and salt water are represented by Cl–Na·Mg or Cl·SO4–Na·Mg. We also observed spatial trends in groundwater depth and total dissolved solids (TDS) concentrations that were opposite to soil salinity, which suggests a certain degree of second-order trend effect. Furthermore, the degree of soil salinization increased and then decreased from the pre-mountain alluvial plain to the Yellow River alluvial plain, while the groundwater chemistry ranged from simple to complex. The most severe area of soil salinization was found to be concentrated between Hongguang and Yaofu, which is also the area where shallow groundwater salinity accumulation is mainly influenced by continental salinization. In summary, this study provides valuable insights into the hydrogeochemical characteristics of the Ningxia Plain, which can inform strategies for mitigating soil salinization and promoting sustainable agriculture development in arid regions.